The aesthetics of Quranic eloquence in verses with similar words, according to Al-Safadi - Ahmad, D. Fahmi Karim Ahmad; Aziz, D. Faridun Ahmad Aziz; Saeed, D. Hawkar Abdul Rahman Saeed (Sulaimani Journal for Humanities, 2025)
The Qur’an, which is the last thing that was revealed from the Allah, He revealed it in a clear Arabic language, full of multiple linguistic phenomena.which can serve as a raw material for linguistic study and research, one of these aspects of the Qur'an is a linguistic study of verses whose wording is very similar. The scholars made it a material for study and searched for the rhetorical and linguistic aspect of that similarity and difference in those verses. And they made every effort to devise that rhetorical purpose for it. One of these scholars is (Abu Al-Barakat Al-Safadi), who died (696 AH), This research dealt with the views of this scholar and discussed them in explaining the linguistic and rhetorical aspect of those verses that have similar words, deducing some results related to those opinions.
Keywords: Quranic linguistics; Arabic rhetoric; Lexical variation; Classical tafsir